The Influence Of Product Quality And Instagram Social Media Promotion On Purchasing Decisions With Semanggi Food Image As A Moderating Variable (Case Study In Generation Z, Surabaya City) - Fetty Asmaniati; Victor Kurniawan Yuwono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of product quality, Instagram social media promotion on buyer decisions with food image as a mediating variable. The research method is quantitative with purposive sampling for generation z in the city of Surabaya. The population in this study was 2,645. The sample consisted of 167 respondents using the Slovin formula. The results found from this research show that Instagram social media, product quality have a significant and positive influence on buyer decisions and food image as an intervention variable has a significant influence. So if the food image's positive value increases or is negative, it also influences the value of Instagram social media and the quality of the product on buyers' decisions. Keywords: Product Quality, Social Promotion Media Instagram Purchase Decision, Food Image